Solitary Skull Metastasis as the First Presentation of a Metachronous Primary Lung Cancer in a Survivor from Pancreatic Cancer - Ali Altalhy; Yazid Maghrabi; Zuhoor Almansouri; Saleh S. Baeesa (Case Reports in Oncological Medicine)
Skull metastasis from lung cancer is relatively common, yet the first presentation for this malignant disease is a rare occurrence. We herein report a case of a 54-year-old female, who had a good outcome following Whipple procedure for periampullary adenocarcinoma five years before her current presentation. During a routine follow-up, she was found to have a slowly progressive painless right parietal swelling. The systemic screening workup revealed no abdominal disease, but a solitary pulmonary nodule was identified. The presence of these two lesions raised the diagnosis of metastases from a previously treated pancreatic adenocarcinoma. The patient underwent complete excision of the skull lesion and subsequent lung biopsy, both of which proved on histopathological examination to be consistent with a primary lung cancer. This case emphasizes the importance of imaging and histopathological correlation in the diagnosis of solitary skull metastases and their effect on the subsequent management.